DEVELOPING SUPPLEMENTARY READING MATERIAL FOR FIRST GRADERS OF RELIGION PROGRAM IN ISLAMIC SENIOR HIGH SCHOOL - Iin Zubaidah (Language-Edu, 2021)
This research aimed to develope supplementary reading material for students of religion program especially in first grade of Al – Khoirot Islamic Senior High School, Malang. According to the researcher’s preliminary study on February 2019 by analyzing the book that used, namely “Bahasa Inggris X” from the government and analyzing the syllabus, the researcher found many problems from the book such as the book used the common English for the students in Senior High School and didn’t focused for specific student, whereas the students of religion program were not interested to study English. The research design of this study was Research and Development (R&D). The development model used by the researcher was ISD model. The procedures include five steps : analyzing the needed materials of the students in religion program, designing the reading materials, develop reading materials for students of religion program consists of Recount text, Narrative Text, and Song lyric, implementing the product which had been developed and evalutating the result of the implementation. The types of data in this research were quantitative and qualitative data. Questionnaire and observation sheet were the instrument used by the researcher. The research finding indicated that based try-out result and the expert judgment, the developing supplementary reading material were acceptable to be taught at the first grade of the religion program students in Islamic  Senior High School.                       Keywords : Supplementary, Reading material, Religion Program.